THEODOXUS FLUVIATILIS (GASTROPODA, NERITIDAE) КАК ЭКОЛОГИЧЕСКИЙ МАРКЕР - (:unkn) unknown (Marine Biological Journal, 2016)
Рассмотрен феномен присутствия Theodoxus fluviatilis в пресноводных и морских водоёмах как биоиндикатора солёности вод. Проанализирована информация о нахождении T. fluviatilis в бассейнах Чёрного, Балтийского и Северного морей, а также критически рассмотрена возможность использования лабораторных опытов по адаптационной способности вида к различной солёности. Материалы бурения в Севастопольской бухте изучены, и результаты сопоставлены с опубликованными данными по хорологии и экологии вида. Присутствие T. fluviatilis в голоценовых морских отложениях бухты и в современной солоноватоводной среде объясняется локализацией моллюсков вблизи источников субмаринной разгрузки подземных вод. Сделан вывод о возможности использования T. fluviatilis в качестве вида – индикатора пресной или солоноватой (до 5 ‰) водной среды.
Theodoxus fluviatilis (Gastropoda, Neritidae) as environmental marker
The phenomenon of Theodoxus fluviatilis presence in freshwater and marine habitats for a possible use of the species as a bioindicator is considered. The information about finding of T. fluviatilis in the basins of the Black, Baltic and North Seas is analyzed, and the possibility of the use of laboratory experiments, connected with the adaptive ability of the species to different salinity, is critically examined. Materials of the drilling in Sevastopol Bay are examined, and the results are compared with the published data on chorology and ecology of the species. The presence of T. fluviatilis in Holocene marine sediments of the Bay and in the contemporary brackish-water environment is explained by the mollusk localization near the sources of the submarine groundwater discharge. The following conclusion is drawn: T. fluviatilis can be used as an indicator species in freshwater or in low brackish (up to 5 ‰) water environment.
Keywords: «оазис»; солёность; стратиграфия; экология; Theodoxus